Capital accumulation through “urban sandboxing”: Exploring planetary urbanization and marginalization in Rome’s urban peripheries - Tomassi, Oliver; Winther, Lars (Informa UK Limited, 2026)
This article explores marginalization in association with market-driven urban restructuring in the urban peripheries of Rome. While urban exclusion is well-documented in European cities, less attention has been paid to the socio-spatial inequalities emerging at the edges of large metropolitan areas. Using qualitative methods and the frameworks of planetary urbanization and urban frontiers, we find that marginalization in Rome is multidimensional, involving infrastructural disconnection, labor market exclusion, and social stigma. To conceptualize these findings, we propose urban sandboxing as a novel framework that captures the tangible and intangible frictions preventing residents from accessing the urban. We invite further research to apply this framework to identify manifestations of capitalist-driven urban exclusion, thereby providing an empirical grounding for the more abstract theory of planetary urbanization.